Harvesting waste heat from cement kiln shell by thermoelectric system. (1st February 2019) - Mirhosseini, Mojtaba; Rezania, Alireza; Rosendahl, Lasse
Abstract: Waste heat recovery in high temperature industries such as cement factory has undeniable benefits. In this study, an annular panel is considered as the thermal absorber around the external surface of the kiln at the location with highest surface temperature along kiln. By using a comprehensive numerical simulation, the temperature on the absorber is obtained and utilized as the hot side boundary condition of thermoelectric generator (TEG) system. For efficient design of the thermoelectric unit on outer surface of the absorber, effect of critical parameters such as thermoelectric leg length and fill factor are studied. Two different thermoelectric materials, bismuth telluride (Bi2 Te3 ) and β-phase zinc antimonide (Zn4 Sb3 ), efficient over different ranges of temperature are considered in order to evaluate electrical power output and performance of the system. Matched power output and conversion efficiency of the system are investigated. A double-objective optimization is carried out to minimize cost per power. The results show, the optimum leg length obtained by analysing cost per power ratio is shorter than the leg length corresponding to the maximum peak power output at a fixed fill factor. Zn4 Sb3 shows higher conversion efficiency at maximum peak power output than Bi2 Te3, except for fill factor of 0.01. Highlights: The best place along the cement rotary kiln for waste heat recovery is found. Design an annular absorber to be used as hot reservoir in a thermoelectric system. Thermal and fluid flow features around absorber circumference is explored by CFD. Mathematical modelling by FEM is developed to design annular TEG unit. Various design parameters and thermoelectric material are studied.